ASSESSING THE EFFECTIVENESS AND SAFETY OF COVID- 19 VACCINES - Adehi, Mary U; Bilkisu , Maijama’a; Habiba , Bala Shuaibu; Abubakar, Muhammad Auwal (Economics and Statistics Research Journal (ESRJ), 2025)
While the coronavirus was a global health crisis, it also generated enormous socio-economic challenges such as trading. Buying and selling, socio-economic meltdown, health sector breakdown. Poor housing facilities. Poverty, unemployment, low income, inequality, and epileptic power supply. Amongst others, in developing countries like Nigeria. This thesis adopts a systemic approach, using a random-effects meta- analysis framework to aggregate findings from peer-reviewed studies conducted between 2021 and 2024 to account for between-study heterogeneity. The pooled overall effect size (exp (b)) was I.658 (95% CI: 1.407- 1.953, P<0.0001) indicating a statistically vaccine effectiveness across the studies. Substantial heterogeneity wvas observed among the studies, as indicated by an [² = 96.8%, which suggests variability in study populations, vaccines types. or methodologies.